2016
DOI: 10.18632/oncotarget.11395
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 enhances HIF-1α target gene expression in human bladder cancer through decreasing its ubiquitin-proteasomal degradation

Abstract: Hypoxia-inducible factor-1α (HIF-1α) can control a transcriptional factor forkhead box P3 (Foxp3) protein expression in T lymphocyte differentiation through proteasome-mediated degradation. In this study, we unveil a reverse regulatory mechanism contributing to bladder cancer progression; Foxp3 expression attenuates HIF-1α degradation. We first demonstrated that Foxp3 expression positively correlates with the metastatic potential in T24 cells and can increase the expression of HIF-1α-target genes, such as vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…We did not detect a change in tgf-β expression (Supplementary Materials, Figure S2K) or IL-10 secretion in H 2 O 2- treated ARPE-19 cells. Therefore, we assumed a proangiogenic function of foxp3 in the cells, as previously reported [22,23]. In line with this, we observed an increase in IL-8 and VEGF-α concentration in the apical supernatant of stressed ARPE-19 cells (Figure 6F,G).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…We did not detect a change in tgf-β expression (Supplementary Materials, Figure S2K) or IL-10 secretion in H 2 O 2- treated ARPE-19 cells. Therefore, we assumed a proangiogenic function of foxp3 in the cells, as previously reported [22,23]. In line with this, we observed an increase in IL-8 and VEGF-α concentration in the apical supernatant of stressed ARPE-19 cells (Figure 6F,G).…”
Section: Resultssupporting
confidence: 88%
“…The signaling pathway is not exactly known so far, but exclusive C5aR1 activation by non-ARPE-19 cell components can be excluded. In regulatory T-cells, the transcription factor FOXP3 promotes the expression of IL-8 [22], and in bladder cancer cells, a knock-down of foxp3 has resulted in the reduced expression of vegf-α [23]. Foxp3 mRNA was expressed in ARPE-19 cells and increased under oxidative stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our observation, the frequency of these FOXP3-expressing cells was much higher in draining lymph nodes from patients with BC compared to other cancers including breast and colon carcinomas [ 7 , 8 ]. The difference may be due to both in situ generation at the tumor site and greater recruitment from the periphery in BC [ 9 , 10 ]. It has been also reported that effector T cells can transiently express FOXP3 after activation.…”
Section: Discussionmentioning
confidence: 99%
“…Jou et al reported that Foxp3, a member of the forkhead/winged-helix family of transcription regulators, enhances expression of VEGF by binding with hypoxia-inducible factor-1α (HIF-1α) [29]. Thus, we evaluated levels of Foxp3 in calycosin-treated MCF-7 and T47D cells.…”
Section: Discussionmentioning
confidence: 99%